Medial habenula cholinergic signaling regulates cocaine‐associated relapse‐like behavior. (12th February 2018) - López, Alberto J.; Jia, Yousheng; White, André O.; Kwapis, Janine L.; Espinoza, Monica; Hwang, Philip; Campbell, Rianne; Alaghband, Yasaman; Chitnis, Om; Matheos, Dina P.; Lynch, Gary; Wood, Marcelo A.
Abstract: Propensity to relapse, even following long periods of abstinence, is a key feature in substance use disorders. Relapse and relapse‐like behaviors are known to be induced, in part, by re‐exposure to drug‐associated cues. Yet, while many critical nodes in the neural circuitry contributing to relapse have been identified and studied, a full description of the networks driving reinstatement of drug‐seeking behaviors is lacking. One area that may provide further insight to the mechanisms of relapse is the habenula complex, an epithalamic region composed of lateral and medial (MHb) substructures, each with unique cell and target populations. Although well conserved across vertebrate species, the functions of the MHb are not well understood. Recent research has demonstrated that the MHb regulates nicotine aversion and withdrawal. However, it remains undetermined whether MHb function is limited to nicotine and aversive stimuli or if MHb circuit regulates responses to other drugs of abuse. Advances in circuit‐level manipulations now allow for cell‐type and temporally specific manipulations during behavior, specifically in spatially restrictive brain regions, such as the MHb. In this study, we focus on the response of the MHb to reinstatement of cocaine‐associated behavior, demonstrating that cocaine‐primed reinstatement of conditioned place preference engages habenula circuitry. Using chemogenetics, we demonstrate that MHb activity is sufficient to induce reinstatement behavior. Together, these data identify the MHb as a key hub in the circuitry underlying reinstatement and may serve as a target for regulating relapse‐like behaviors. Abstract : The medial habenula is a region typically regarded as a mediator of aversion, anxiety‐like behaviors, and the aversive properties of nicotine. Here, we demonstrate that the medial habenula is engaged by reinstatement of cocaine‐associated behavior. Moreover, we show that chemogenetic activation of the cholinergic habenula population induces reinstatement of cocaine CPP.